Psychotherapy of Dependent Personality Disorder: The Relationship of Patient–Therapist Interactions to Outcome. Issue 2 (2nd April 2020) - Maccaferri, Giorgio E.; Dunker-Scheuner, Daniela; De Roten, Yves; Despland, Jean-Nicolas; Sachse, Rainer; Kramer, Ueli
Abstract : Objective: So far, only a few studies have focused on psychotherapy for Dependent Personality Disorder (DPD). DPD is marked by a repetitive pattern of efforts aiming at maintaining close relationships, which may present as a lack of assertiveness and as a difficulty in making routine decisions. The present study aims at exploring processes of change taking place during the working phase of a clarification-oriented psychotherapy (COP) by focusing on the in-session patient–therapist interaction, as it changes during treatment and their links with treatment outcome. Methods: N = 74 patients with DPD were recruited in a naturalistic setting; they underwent long-term COP. Sessions 15, 20 and 25 were video- or audio-recorded and analyzed using the Process-Content-Relationship Scale, an observer-rated instrument that measures the quality of the interaction processes from patient's and therapist's perspectives. Therapy outcomes were assessed with the Personality Inventory – Dependency Subscale, Beck Depression Inventory, Inventory of Interpersonal Problems and Self-efficacy Scale at intake and discharge of therapy. Three-level Hierarchical Linear Modeling was applied to test the hypotheses. Results : Improvement in interaction processes was observed in all patient's and therapist's variables over the sessions 15, 20, 25. Overall, this increase in quality of interaction process was unrelated with outcome, but decrease in dependency traits was predicted by increase in therapist's quality of relationship offer, understanding of content and directivity over the course of the working phase of COP. Conclusions : Studying interaction processes in DPD provides an initial understanding of differential roles of potential mechanisms of change in effective treatment.